Carbohydrate Composition and Water-Stable Aggregation of an Oxisol as Affected by Crop Sequence under No-Till - Martins, Marcio dos Reis [UNESP]; Angers, Denis A.; Cora, Jose Eduardo [UNESP] (Soil Sci Soc Amer, 2012)
In no-till systems, plants play a substantial role in soil physical conditioning because physical management is otherwise confined to sowing operations. We performed a study to determine the effect of 28 different crop sequences on soil water-stable aggregation, soil organic C (SOC), and the neutral carbohydrate composition of the surface layer (0-5-cm depth) of an Oxisol under no-till. Summer crop sequences with corn (Zea mays L.) on a continuous basis or in rotation with soybean [Glycine max (L.) Merr.] showed a higher mean weight diameter (MWD) of water-stable aggregates than those with a rice (Oryza sativa L.)-bean (Phaseolus vulgaris L.)-cotton (Gossypium hirsutum L.) rotation. Among winter crops, pearl millet [Pennisetum americanum (L.) Leeke] or grain sorghum [Sorghum bicolor (L.) Moench] were associated with a higher MWD than oilseed radish (Raphanus sativus L. var. oleiformis Pers.). Plant tissues of Poaceae species (corn, pearl millet, and sorghum) were enriched in pentoses relative to other plant species. A principal component analysis showed a close positive relationship of the soil aggregate MWD with the soil xylose content, but not with other soil monosaccharide and SOC contents, and a positive relationship with the amount of pentose input to the soil, notably from aboveground plant materials. A possible explanation is that pentosans are used as an energy source by filamentous microorganisms, which play a well-known role in stabilizing soil aggregates. Our results suggest that plant-derived carbohydrates mediate crop species effects on soil structure under no-till conditions, and this effect appears to be independent of changes in total SOC.